EVALUATION OF POMEGRANATE PEEL AS A SUBSTRATE FOR CITRIC ACID PRODUCTION BY ASPERGILLUS NIGER - SUTRADHAR, PAYEL; SAHA, ISHIKA; CHAKRAVARTY, AMIT (International Journal of Current Pharmaceutical Research, 2020)
Objective: The present study aimed to evaluate dried pomegranate peels as a substrate for citric acid production by Aspergillus niger. Methods: The morphological study of Aspergillus niger was carried out by wet mount with lactophenol cotton blue and slide culture method. A preliminary qualitative screening of citric acid-producing ability of this fungal strain was also performed by using the Czapek-Dox agar medium containing Bromocresol green. Dried and finely powdered Pomegranate peel was used as a principal substrate for the production of citric acid by submerged fermentation. Classical method of citric acid recovery involved a precipitation technique using calcium hydroxide followed by filtration and subsequent treatment with sulphuric acid. The citric acid produced was also chemically detected and titrimetrically estimated by 0.1 N NaOH. Results: The present experiment demonstrated that pomegranate peels may serve as an inexpensive medium for the production of citric acid with a yield of 19.39 g/l by using Aspergillus niger. Conclusion: This study provided an alternative basis to recycle the fruit peel waste of pomegranate in order to achieve industrially feasible and environmentally sustainable bio-production of pharmaceutically significant citric acid.